Students’ in-class impression management: Comparing models for measuring student strategies of self-presentation - Forster-Heinzer, Sarah; Nagel, Arvid; Biedermann, Horst; Reichenbach, Roland (Frontiers in Education, 2023)
This paper addresses an issue that has largely been neglected in educational research so far: students’ impression management. Impression management is defined as an individual’s active effort to present the self in a certain, usually positive way. Owing to a lack of empirical studies on students’ impression management at class, we primarily pursued the basic aim of designing an instrument for analyzing deliberate student tactics of self-presentation. Its development was based on work on school-specific coping strategies. Construct validity and criterion validity were tested in a sample consisting of 201 Austrian high school students. The results indicated that a correlative five-dimensional factor structure fit the data best. Furthermore, students with higher scores on the presented and appearing self also scored higher on most dimensions of the Impression Management scale than their peers who cared less about their teacher’s perception. These findings raise the question of what types of impression management can be deemed functional with respect to academic success.